Attitude of Laities Towards Sraddha Ritual Among the Buddhist Community of Jyapu - Dangol, Rabindra (Journal of Buddhist Studies (T.U.), 2025)
The research observes the practice of annual sraddha within the Jyapu Community, an ethnic group in Kathmandu known for its rich cultural heritage, arts, and rituals. The research examines the attitude of the general public towards sraddha ritual. The research findings show that annual sraddha rituals are still regularly practiced in Kathmandu. However, the core philosophy behind these rituals appears to have significantly deteriorated over time. The confusion has been clearly observed among the laities. For example, 91% of the respondent prefers Bajracharya priest for performing rituals including sraddha,however, 57% only accepted them as a Buddhist. Hence, if majority of the Buddhist respond themselves as a Buddhist by knowing themselves correctly in the census then data wise alsoBuddhist population will be increased in Nepal.